Fisheries resource management of the daggertooth pike conger, Muraenesox cinereus, using existing limited datasets in the western Seto Inland Sea, Japan. (25th October 2014) - Watari, S.; Murata, M.; Baba, T.; Oda, S.; Ishitani, M.; Mishiro, K.; Uchida, Y.
Abstract The daggertooth pike conger, Muraenesox cinereus (Forsskål), has become an important fish resource in the western Seto Inland Sea, Japan, since the 1990s. However, introducing sustainable fisheries resource management for this species is difficult in this region because stock assessments have not been performed, and official fisheries statistics for this stock were discontinued after 2007. This study used existing limited data sets to compile the first report for fisheries resource management for this M. cinereus stock. Yield‐per‐recruit analyses showed that increasing fishing pressure above current levels would provide only a minimal increase in expected catch levels. Hence, the current harvest level is considered to represent the upper limit of fishing pressure. Age composition in a given year could potentially be used to forecast landing abundance for the following 2 years. This study provides a basis for establishing effective fisheries resource management strategies for M. cinereus.